The Blockchain-enabled Supply Chain and Its Impact on Sourcing and Transactional Functions of the Procurement Process - Sulíková, Barbora (2018)
The amount of outsourced operations has elevated and supply chains transformed predominantly into global networks. Hence, challenges and bottlenecks critical to business continuation are present in procurement functions. The relevance of procurement in supply chain practice has uplifted due to its significant ability to enhance competitive advantage. Regardless of the past digitalization efforts, low level of transparency and cross-network collaboration characterizes procurement processes. Blockchain as an innovative technology has the potential to significantly disrupt complex supply chains. However, the impact of blockchain solution on individual supply chain processes has been omitted from existent academic and non-academic literature. Due to the strategic importance of and challenges related to procurement function, this research examines blockchain’s significance for sourcing and transactional functions of procurement. Method used for this purpose is qualitative research based on six expert semi-structured interviews, performed through audio-video device. In terms of data analysis, interpretive approach of qualitative content analysis was conducted to deliver major findings. Overall, the potential of blockchain solution for improvement of both sourcing and transactional functions of the procurement is substantial, with implications in varying areas. Blockchain is a valuable solution, simplifying the operations and management, making the entire process of procurement more efficient.